Real time underlying inflation gauges for monetary policymakers - Marlene Amstad; Simon Potter (Federal Reserve Bank of New York, 2009)
Central banks analyze a wide range of data to obtain better measures of underlying inflationary pressures. Factor models have widely been used to formalize this procedure. Using a dynamic factor model this paper develops a measure of underlying inflation (UIG) at time horizons of relevance for monetary policymakers for both CPI and PCE. The UIG uses a broad data set allowing for high-frequency updates on underlying inflation. The paper complements the existing literature on U.S. 'core' measures by illustrating how UIG is used and interpreted in real time since late 2005.
Keywords: C13; C33; C43; E31; E37; 330; Inflation; dynamic factor models; core inflation; monetary policy; forecasting